The Experimental Therapy on Brain Ischemia by Improvement of Local Angiogenesis with Tissue Engineering in the Mouse. Issue 1 (January 2014) - Ju, Rongkai; Wen, Yujun; Gou, Rongbin; Wang, Ying; Xu, Qunyuan
Neural restoration has proven to be difficult after brain stroke, especially in its chronic stage. This is mainly due to the generation of an unpropitious niche in the injured area, including loss of vascular support but production of numerous inhibitors against neuronal regeneration. Reconstruction of a proper niche for promoting local angiogenesis, therefore, should be a key approach for neural restoration after stroke. In the present study, a new biomaterial composite that could be implanted in the injured area of the brain was created for experimental therapy of brain ischemia in the mouse. This composite was made using a hyaluronic acid (HA)-based biodegradable hydrogel scaffold, mixed with poly(lactic- co -glycolic acid) (PLGA) microspheres containing vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang1), two factors that stimulate angiogenesis. In addition, the antibody of Nogo receptor (NgR-Ab), which can bind to multiple inhibitory myelin proteins and promote neural regeneration, was covalently attached to the hydrogel, making the hydrogel more bioactive and suitable for neural survival. This composite (HA–PLGA) was implanted into the mouse model with middle cerebral artery occlusion (MCAO) to explore a new approach for restoration of brain function after ischemia. A good survival and proliferation of human umbilical artery endothelial cells (HUAECs) and neural stem cells (NSCs) were seen on the HA hydrogel with PLGA microspheres in vitro. This new material was shown to have good compatibility with the brain tissue and inhibition to gliosis and inflammation after its implantation in the normal or ischemic brain of mice. Particularly, good angiogenesis was found around the implanted HA–PLGA hydrogel, and the mouse models clearly showed a behavioral improvement. The results in this present study indicate, therefore, that the HA–PLGA hydrogel is a promising material, which is able to induce angiogenesis in the ischemic region by releasing VEGF and Ang1, thus creating a suitable niche for neural restoration in later stages of stroke. This manuscript is published as part of the International Association of Neurorestoratology (IANR) special issue of Cell Transplantation .